Move Analysis of Tourism Research Article Abstracts in National and International Journal Articles - Nurul Aini Akrima Sabila, - (2020)
This study aims to investigate the moves of tourism research article abstracts from national and international journals. Employing Hyland's (2000) model, the data analyzed were 120 tourism research article abstracts from journals indexed by Scopus (international) and Sinta (national). The results show that there are different preferences in terms of move realization in tourism research article abstracts. For national journal abstracts, Introduction move is preferred and Conclusion move is likely to be excluded. Hence, the most recurring pattern in Sinta is Introduction-Purpose-Method-Product. On the contrary, international journal abstracts tend to include Conclusion move and leave out Introduction move, and thus, the preferred pattern in Sinta is Purpose-Method-Product-Conclusion. This study provides insights for tourism practitioners regarding the characteristics of the expected abstracts from different indexation levels to consider before submitting their research article abstracts to their choice of publishers.